The molecular and phenotypic spectrum of IQSEC2‐related epilepsy. (26th September 2016) - Zerem, Ayelet; Haginoya, Kazuhiro; Lev, Dorit; Blumkin, Lubov; Kivity, Sara; Linder, Ilan; Shoubridge, Cheryl; Palmer, Elizabeth Emma; Field, Michael; Boyle, Jackie; Chitayat, David; Gaillard, William D.; et al.
Summary: Objective: IQSEC2 is an X‐linked gene associated with intellectual disability (ID) and epilepsy. Herein we characterize the epilepsy/epileptic encephalopathy of patients with IQSEC2 pathogenic variants. Methods: Forty‐eight patients with IQSEC2 variants were identified worldwide through Medline search. Two patients were recruited from our early onset epileptic encephalopathy cohort and one patient from personal communication. The 18 patients who have epilepsy in addition to ID are the subject of this study. Information regarding the 18 patients was ascertained by questionnaire provided to the treating clinicians. Results: Six affected individuals had an inherited IQSEC2 variant and 12 had a de novo one (male‐to‐female ratio, 12:6). The pathogenic variant types were as follows: missense (8), nonsense (5), frameshift (1), intragenic duplications (2), translocation (1), and insertion (1). An epileptic encephalopathy was diagnosed in 9 (50%) of 18 patients. Seizure onset ranged from 8 months to 4 years; seizure types included spasms, atonic, myoclonic, tonic, absence, focal seizures, and generalized tonic–clonic (GTC) seizures. The electroclinical syndromes could be defined in five patients: late‐onset epileptic spasms (three) and Lennox‐Gastaut or Lennox‐Gastaut–like syndrome (two). Seizures were pharmacoresistant in all affected individuals with epileptic encephalopathy. The epilepsy in the other nine patients had a variable age at onset from infancy to 18 years; seizure types included GTC and absence seizures in the hereditary cases and GTC and focal seizures in de novo cases. Seizures were responsive to medical treatment in most cases. All 18 patients had moderate to profound intellectual disability. Developmental regression, autistic features, hypotonia, strabismus, and white matter changes on brain magnetic resonance imaging (MRI) were prominent features. Significance: The phenotypic spectrum of IQSEC2 disorders includes epilepsy and epileptic encephalopathy. Epileptic encephalopathy is a main clinical feature in sporadic cases. IQSEC2 should be evaluated in both male and female patients with an epileptic encephalopathy.